The Differences Between Scientific Knowledge and other Forms of Knowledge - Abdul Shamhuna (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
This dissertation looks at the differences between scientific knowledge and other types, like philosophical, experiential, and traditional knowledge. It focuses on the guidelines and structures that separate these systems. Using methods like interviews, surveys, and a review of relevant literature, the study shows that scientific knowledge relies on evidence and repeatability, while other types of knowledge value personal experience, context, and cultural importance. Important findings reveal that healthcare workers often appreciate combining different types of knowledge to improve patient care, suggesting a move toward a more complete approach. These findings are significant because they could shape healthcare practices that honour various types of knowledge, leading to a better understanding of patient needs and wishes. Moreover, the study has wider relevance for health policy and education, promoting the inclusion of different perspectives in medical training and practice. By encouraging communication between scientific and non-scientific knowledge systems, the research highlights the importance of cultural awareness and the need for flexible healthcare models that respect and integrate various forms of knowledge. This could ultimately enhance healthcare results and create a more inclusive approach to patient care.